Konsep Tazkiyatun Nafs dalam Bimbingan Konseling Islam: Pendekatan Spiritual Terhadap Kesehatan Mental - Sholihuddin Sholihuddin (Yayasan Mutiara Hati Moeslem, 2025)
This study aims to explore the effectiveness of Tazkiyatun Nafs as a spiritual approach in Islamic counseling to address mild to moderate mental disorders. Using a descriptive qualitative method, data were collected through in-depth interviews and literature studies, then analyzed using a thematic content analysis approach. The results show that the stages of Takhalli, Tahalli, and Tajalli significantly assist participants in emotional regulation, self-reflection, and the enhancement of spiritual awareness. These findings contribute to the development of Sufi-based Islamic counseling theory and open the possibility for integrating this approach into Islamic education and psychological services. The study recommends Tazkiyah-based counselor training and further exploration with broader populations and methodologies to strengthen the validity of this model.